2005
DOI: 10.1093/brief-treatment/mhi014
|View full text |Cite
|
Sign up to set email alerts
|

Measured Response to Identified Suicide Risk and Violence: What You Need to Know About Psychiatric Patient Safety

Abstract: Within inpatient psychiatric settings exists evidence of a significant risk of violent incidents and incidents of deliberate self-harm. One of the most hidden and preventable mental health problems is the fact that approximately 1,500 suicides take place annually in inpatient hospital facilities throughout the United States. This article focuses on the advantages and disadvantages of risk and suicide assessment procedures while attempting to answer the following questions: What degree of risk currently exists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Psychiatric research has shown that leadership comprises three primary areas: experience, availability and understanding the patient safety plan. It is the willingness to examine the reasoning behind rule development in advocacy of the patient and to see the environment as interactive part of the patient care (Yeager et al . 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychiatric research has shown that leadership comprises three primary areas: experience, availability and understanding the patient safety plan. It is the willingness to examine the reasoning behind rule development in advocacy of the patient and to see the environment as interactive part of the patient care (Yeager et al . 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The patient mix of each unit is also connected to patient safety (O'Brien & Cole 2003). Providing a mixture of diagnosis and levels of acuity in units can distribute the workload and enhance patient safety (Yeager et al . 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of suicide attempts occurring in inpatient units is also a major concern and is the second most common sentinel event—defined as an unexpected occurrence involving death or serious physical or psychological injury, or the risk thereof—reported to the Joint Commission on Accreditation of Healthcare Organizations (JCAHO) 6. Approximately 1,500 suicides occur in inpatient hospital units in the US each year, and a staggering one-third of these take place while the patient is on 15-minute checks 7, 8. The JCAHO emphasized the need for around-the-clock observation for inpatients at high risk for suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies further expand on ways to decrease suicides through the limitation of access to means (Lieberman, Resnik, & Holder‐Perkins, 2004; Sullivan et al., 2005; Yeager et al., 2005). Yeager and colleagues, who published one of the most comprehensive articles on environmental safeguards, point out that 62–75% of inpatient suicides were due to either hanging or jumping from high places; therefore, this emphasizes the importance of setting both competent suicide assessments and systematic safety protocols as a priority.…”
Section: History Of Environmental Safeguardsmentioning
confidence: 99%